2022
DOI: 10.1099/mic.0.001153
|View full text |Cite
|
Sign up to set email alerts
|

Alternaria alternata as endophyte and pathogen

Abstract: Alternaria alternata is a common species of fungus frequently isolated from plants as both an endophyte and a pathogen. Although the current definition of A. alternata rests on a foundation of morphological, genetic and genomic analyses, doubts persist regarding the scope of A. alternata within the genus due to the varied symbiotic interactions and wide host range observed in these fungi. These doubts may be due in large part to the history of unstable taxonomy in Alternaria, based on limited morphological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 159 publications
1
30
0
Order By: Relevance
“…Likewise, fungal communities were more sensitive and highly affected by the plant host, compartments, and fertilizer treatments. The majority of Fusarium and Alternaria species in the Ascomycota division are the most significant plant pathogens, these endophytes are capable of producing mycotoxins in cereal crops like rice and potentially affecting human health through the food chain (Fones et al, 2020;Demers, 2022). Interestingly, we found that the application of silicate and biofertilizer suppresses the relative abundance of such pathogens, Alternaria and Fusarium.…”
Section: Discussionmentioning
confidence: 77%
“…Likewise, fungal communities were more sensitive and highly affected by the plant host, compartments, and fertilizer treatments. The majority of Fusarium and Alternaria species in the Ascomycota division are the most significant plant pathogens, these endophytes are capable of producing mycotoxins in cereal crops like rice and potentially affecting human health through the food chain (Fones et al, 2020;Demers, 2022). Interestingly, we found that the application of silicate and biofertilizer suppresses the relative abundance of such pathogens, Alternaria and Fusarium.…”
Section: Discussionmentioning
confidence: 77%
“…The species of Lecanicillium are known to be entomopathogens, mycoparasites, or endophytes [ 78 , 79 ]. Alternaria species are ubiquitous in the environment, with a number of species being major plant pathogens, saprophytes, endophytes, and opportunistic pathogens or allergens of humans [ 80 , 81 , 82 ]. As the leaf samples used in this study did not show any discernable symptoms of fungal disease, it is likely that the fungal strains isolated in this study are plant endophytic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…The ITS region is widely accepted in the mycology community as the DNA barcoding marker with the highest probability for the precise identification of a broad range of fungal species ( Schoch et al, 2012 ; Raja et al, 2017 ). A. alternata species are commonly isolated in plants existing as endophytes or pathogens and they display varied symbiotic lifestyles and wide host ranges ( Lou et al, 2013 ; De Mers, 2022 ). Fungal species such as A. alternata which are broadly delineated due to their unstable taxonomy and limited morphological characteristics for species delimination, are often further delineated using phylogenetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In our phylogenetic analysis of the three fungal isolates it was revealed that these isolates closely cluster with Alternaria species. However, for A. alternata there are few clades, thus limiting the power of further species delineation using evolutionary relationship ( De Mers, 2022 ). Endophytic isolates of A. alternata have been shown to exist as asymptomatic symbionts with no apparent ability to cause plant disease ( Spurr and Welty, 1975 ).…”
Section: Discussionmentioning
confidence: 99%